Review paperFlupirtine in management of low back pain - Szechliński, Jacek; Styczyński, Tadeusz; Świerkot, Jerzy; Szmyrka-Kaczmarek, Magdalena (Reumatologia/Rheumatology, 2007)
Low back pain is commonly encountered in primary care practice and rheumatological practice but the specific cause often cannot be identified. Serious causes that need to be considered include infection, malignancy, rheumatologic diseases and neurologie disorders. The following drug groups principally can be applied for back pain: non-opioid analgesic (acetaminophen, nonsteroidal anti-inflammatory drugs), muscle relaxants, opioid analgesic, antidepressants. Another drug is flupirtine a centrally acting non-opioid analgesic. Flupirtine has a specific mode of action as selective neuronal potassium channel opener and shows analgesic, muscle tone normalisation properties and protects from pain chronification